Digital Gaming Habits and EFL Learning In Primary Education: A Bibliometric Analysis - Annisa Putri; Ellianawati Ellianawati; Bambang Subali (JURNAL ASIMILASI PENDIDIKAN, 2026)
Digital gaming has become increasingly integrated into students’ daily activities, including in the context of learning English as a Foreign Language (EFL). However, previous studies have predominantly focused on the use of games in formal learning through game-based learning approaches, while studies examining digital gaming habits as part of students’ everyday experiences remain relatively limited. Therefore, this study aims to analyze research trends, influential contributors, and conceptual themes related to digital gaming and EFL learning. This study employed a bibliometric approach using data collected from Scopus and Crossref through Publish or Perish. A total of 238 documents published between 2022 and 2026 were analyzed using VOSviewer through keyword co-occurrence, cluster analysis, and overlay visualization. The findings indicate that research on digital gaming and EFL learning has continued to develop in recent years, although most studies still focus on formal game-based learning environments. Visualization analysis revealed strong relationships among digital games, vocabulary learning, young learners, and psychology. In addition, recent research trends have shifted toward more contextual and student-centered topics, such as incidental learning and digital play. Overall, this study highlights that digital gaming has the potential to support English language acquisition through natural language exposure in students’ daily digital activities.